FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PRODUSEN ROTI SKALA KECIL DAN MENENGAH DI KOTA BALIKPAPAN TAHUN 2011 - Karna, L.B Erlangga; Susilo, Y Sri (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2013)
Tis research aims to identify and analyze the factors that afect revenue producers in the Balikpapan City bakery . Primary data were obtained from feld surveys . Number of respondents by 50 merchants . Te analysis tool is an econometric technique used ordinary least square ( OLS ). Conclusions of the research are : ( 1 ) Variable production valuesÃ‚Â and a signifcant positive efect on the income of bread producers in the Balikpapan city . ( 2 ) Variable hours employees work in a positive and signifcant efect on the income of bread producers in the Balikpapan city . ( 3 ) Variable long efort not signifcantly afect earnings bread producers in the Balikpapan city . ( 4 ) education variable does not signifcantly afect earnings bread producers in the Balikpapan city . ( 5 ) business dummy variable that is the number of employees does not signifcantly afect earnings bread producers in the Balikpapan city.Keywords:Ã‚Â earnings, hours of work, length of business , education , number of employees